Review: Potensi Susu Kuda dan Produk Turunannya sebagai Pangan Fungsional serta Potensi dibidang Kesehatan: Potential of Mare Milk and Its Derivatives as Functional Food and Health Benefits Potential-A review - Fajriani, Laksmi Nur; Anisah, Anisah; Isasih, Widani Darma (Universitas Bumigora, 2024)
Mare milk is a type of milk that is widely consumed in several Asian and Eastern European countries and has the potential to be developed into functional food. In several countries such as Mongolia and Kazakhstan, Mare milk is widely consumed in the form of fresh milk or fermented milk which is usually called koumiss, while in Indonesia it is still widely consumed in the form of natural fermented milk. However, horse milk is not as popular as cow's milk or other types of milk, so it is necessary to develop products from mare milk, so that they are more accepted. The aim ofthis study is to explain the products that can be developed from mare milk and their potential in the health sector. The method used was a literature review with a descriptive approach using secondary literature through fourth steps, namely identification, screening, eligibility, included and a review process to obtain 16 articles. The finding of this study show that mare milk has begun to be developed into several products such as koumiss, yogurt, and dangke . Some of these products are fermented products. It's just that improvements are needed in terms of sensory characteristics to increase the level of acceptance because mare milk has a distinctive taste and aroma. Apart from that, mare milk is also known to have potential health benefits as an antibacterial, improving the digestive tract, and lowering cholesterol.